A European multicentre survey of impulse control behaviours in Parkinson's disease patients treated with short‐ and long‐acting dopamine agonists. (11th May 2016) - Rizos, A.; Sauerbier, A.; Antonini, A.; Weintraub, D.; Martinez‐Martin, P.; Kessel, B.; Henriksen, T.; Falup‐Pecurariu, C.; Silverdale, M.; Durner, G.; Røkenes Karlsen, K.; Grilo, M.; et al.
Abstract : Background and purpose: Impulse control disorders (ICDs) in Parkinson's disease (PD) are associated primarily with dopamine agonist (DA) use. Comparative surveys of clinical occurrence of impulse control behaviours on longer acting/transdermal DA therapy across age ranges are lacking. The aim of this study was to assess the occurrence of ICDs in PD patients across several European centres treated with short‐ or long‐acting [ropinirole (ROP); pramipexole (PPX)] and transdermal [rotigotine skin patch (RTG)] DAs, based on clinical survey as part of routine clinical care. Methods: A survey based on medical records and clinical interviews of patients initiating or initiated on DA treatment (both short‐ and long‐acting, and transdermal) across a broad range of disease stages and age groups was performed. Results: Four hundred and twenty‐five cases were included [mean age 68.3 years (range 37–90), mean duration of disease 7.5 years (range 0–37)]. ICD frequencies (as assessed by clinical interview) were significantly lower with RTG (4.9%; P < 0.05) compared with any other assessed DAs except for prolonged release PPX (PPX‐PR). The rate of ICDs for PPX‐PR (6.6%) was significantly lower than for immediate release PPX (PPX‐IR) (19.0%; P < 0.05). Discontinuation rates of DA therapy due to ICDs were low. Conclusion: Our data suggest a relatively low rate of ICDs with long‐acting or transdermal DAs, however these preliminary observational data need to be confirmed with prospective studies controlling for possible confounding factors. Abstract : Clickhere for the corresponding questions to this CME article.